The bat ebook - Nesbo, Jo (Harry Hole, 2013)
INTERNATIONAL BESTSELLER • In the electrifying first installment of the New York Times bestselling series, Harry Hole of the Oslo Crime Squad is dispatched to Sydney to observe a murder case. As he circles closer to the killer, Harry begins to fear that no one is safe, least of all those investigating the murder. The victim is a twenty-three year old Norwegian woman who is a minor celebrity back home. Harry is free to offer assistance, but he has firm instructions to stay out of trouble. Never one to sit on the sidelines, Harry befriends one of the lead detectives, and one of the witnesses, as he is drawn deeper into the case. Together, they discover that this is only the latest in a string of unsolved murders, and the pattern points toward a psychopath working his way across the country.